Corpo e masculinidade na revista VIP Exame Body and masculinity in the magazine VIP Exame - Marko Monteiro (Cadernos Pagu, 2001)
Nesse artigo elaboro comentários teóricos acerca de novas formas de se vivenciar a corporalidade presentes contemporaneamente, a partir da análise da revista masculina VIP Exame. O texto baseia-se numa pesquisa que incluiu uma observação dentro da redação da revista e análise de materiais impressos, centrando-se na forma como a revista aborda o corpo masculino e coloca a preocupação com a aparência como importante para uma masculinidade bem sucedida. Com base nestes dados busco avaliar, a partir de perspectivas feministas e sobre o corpo, a influência do valor dado ao corpo e ao seu monitoramento reflexivo na constituição de identidades de gênero. In this article I elaborate theoretical comments on the subject of corporeality and the new forms of experiencing the body that are present in contemporary times. On the basis of a research with a Brazilian men's magazine, VIP Exame, which involved the analysis of issues of the magazine as well as an observation of the working process of the reporters and journalists, I focus my comments on the way the masculine body is treated by the magazine and how a discourse emerges on masculinity where attention to "good looks" becomes an important feature of a successful masculinity. On the basis of these observations I go on to discuss feminist and other theories of the subject, in order to understand how the reflexive monitoring of the body is increasingly important in the constitution of gender identities.